Relationship between Energy-Protein Intake and Nutritional Status in Infected Toddlers Acute Respiratory Tract (ISPA) at the Mulyorejo Community Health Center, Surabaya - Quddus, Choridatul (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The direct causes of nutritional status are food consumption and infectious diseases. Inadequate foodconsumption reduces the absorption of nutrients such as energy and protein. Energy is created through themetabolism of carbohydrates, fats, and proteins which function as energy substances for metabolism.Proteins also help make antibodies in the body so that the body is not easily attacked by infectious diseases.This research aims to find out how the nutritional status of toddlers suffering from acute respiratoryinfections (ARI) at the Mulyorejo Community Health Center, Surabaya, correlates with their energy andprotein intake.This quantitative correlational research uses a cross-sectional design. This study was conducted in theMulyorejo Community Health Center working area with respondents of 35 toddlers who were registered atthe Mulyorejo Community Health Center in February and March and their mothers or caregivers. Data wascollected through filling out questionnaires with interviews. Questionnaires were used to collectrespondents' identities and toddlers' energy and protein intake. By using the weight for age index, thenutritional status of toddlers is measured by weighing them directly. The research instrument has beenvalidated by lecturers who are experienced in this field. The data analysis method is the Rank-Spearmantest.The results of the Rank-Spearman analysis showed that there was a relationship between the nutritionalstatus of ISPA toddlers and energy intake (p=0.044) and protein intake (p=0.045). The author's advice isthat mothers should pay attention to what their toddlers eat so that they stay healthy.